Experimental and numerical investigations of multi-layered ship engine room bulkhead insulation thermal performance under fire conditions - Pham Thanh-Nhut; Le Quoc Tien; Do Quang Thang (Curved and Layered Structures, 2024)
The thermal insulation layer of the ship’s engine room bulkhead is typically constructed from multiple layers of mineral wool. This layer is designed to keep the temperature on the surface of the bulkhead below 140°C in case of a fire. However, measuring the inner and external temperatures of each wall panel bulkhead type during a fire can be difficult. To address this issue, this study was conducted to evaluate the multilayer heat transfer capability of the bulkhead insulation in the event of an engine room fire. The study used heat transfer theory, experimental models, and numerical analysis to assess nine bulkhead insulation specimens. These specimens were fabricated from three original specimens and included a 10–30 mm air layer (W-75, W-50, and W-25). The results showed that all improved specimens had better thermal insulation than the originals. Among them, the improved specimens derived from the W-25 specimen exhibited the most significant temperature reduction compared to those derived from the W-75 and W-50 specimens. The results demonstrated a slight difference between the three methodologies, indicating a high level of reliability in the research findings.